The effect of aging on the bone healing properties of blood plasma. Issue 7 (July 2021) - Al-Hamed, Faez Saleh; Rodan, Rania; Ramirez-Garcialuna, Jose Luis; Elkashty, Osama; Al-Shahrani, Nasser; Tran, Simon D; Lordkipanidzé, Marie; Kaartinen, Mari; Badran, Zahi; Tamimi, Faleh
Highlights: Plasma composition changes with age and this influences its role on bone healing. The local application of young plasma enhanced bone healing compared to old plasma. These findings could partially explain the reduced healing capacity seen in aged patients and can be used to develop new biological materials for better bone regeneration. Abstract: Objectives: Age-related changes in blood composition have been found to affect overall health. Thus, this study aimed to understand the effect of these changes on bone healing by assessing how plasma derived from young and old rats affect bone healing using a rat model. Methods: . Blood plasma was collected from 6-month and 24-month old rats. Differences in elemental composition and metabolome were assessed using optical emission spectrometry and liquid mass spectrometry, respectively. Bilateral tibial bone defects were created in eight rats. Young plasma was randomly applied to one defect, while aged plasma was applied to the contralateral one. Rats were euthanized after two weeks, and their tibiae were analyzed using micro-CT and histology. The proteome of bone marrow was analyzed in an additional group of three rats. Results: Bone-defects treated with aged-plasma were significantly bigger in size and presented lower bone volume/tissue volume compared to defects treated with young-plasma. Histomorphometric analysis showed fewer mast cells, macrophages, and lymphocytes in defects treated with old versus young plasma. The proteome analysis showed that young plasma upregulated pathways required for bone healing (e.g. RUNX2, platelet signaling, and crosslinking of collagen fibrils) whereas old plasma upregulated pathways, involved in disease and inflammation (e.g. IL-7, IL-15, IL-20, and GM-CSF signaling). Plasma derived from old rats presented higher concentrations of iron, phosphorous, and nucleotide metabolites as well as lower concentrations of platelets, citric acid cycle, and pentose phosphate pathway metabolites compared to plasma derived from young rats. Conclusion: bone defects treated with plasma-derived from young rats showed better healing compared to defects treated with plasma-derived from old rats. The application of young and old plasmas has different effects on the proteome of bone defects.